Pengaruh teknik membaca skimming terhadap minat baca siswa kelas XI SMK Islam Fatahillah - Siti Nurbaecih; Ni Wayan Ayu Permata Sari; Yayan Sudrajat (Asosiasi Dosen Pemerhati Pendidikan Indonesia, 2022)
This study aims to explain the influence of the use of the Skimming Method Technique on the Reading Interest of Class XI Students at Fatahillah Islamic Vocational School Jakarta in the 2020/2021 Academic Year. The population of this study were all students of class XI SMA Islam Fatahillah as many as 50 people. Samples were taken as a whole, namely 35 people, 15 people for the experimental class and 20 people for the control class. The research method used in this research is quantitative with correlational research design. The instrument used aims to detect the extent to which variations in a factor are related to variations in one or more other factors based on the correlation coefficient. Based on the calculation results, the total scores of the variables X and Y are entered into the product moment correlation formula to connect the scores. Thus obtained, rxy = 0.95. The magnitude of the contribution of X and Y is seen from the magnitude of the coefficient number with a determination of r, which is 0.9025 or 90.25%. Based on the results of data analysis, it was obtained that r arithmetic was greater than r table (0.95 > 0.334) this indicates that there is a significant influence between the skimming method on reading interest in class XI students of Fatahillah Islamic Vocational School Jakarta in the 2020/2021 learning year. Keywords : Skimming method, reading interest, students influence